Protection of Health Insurance Rights for Children with Disabilities in the City of Semarang: Case Study at Double Disability Orphanage Semarang - Rizqi Amanullah; Budi Sarwo; Muhammad Nasser (SOEPRA, 2019)
Children with disabilities have equal opportunity in obtaining health insurance through the Government's National Health Insurance (Jaminan Kesehatan Nasional) program organized by Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan. This study aims to find out the protection of the right to health insurance for children with disabilities. The legal status of children with disabilities within the framework of the National Health Insurance as mandated in the 1945 Constitution of the State of the Republic of Indonesia Article 28 (h) paragraph (1) and Article 34 paragraph (2) have not been explicitly stated in the legislation in below it.This research uses sociological juridical approach and qualitative research method. The data used are primary data and secondary data through field study and literature study. The field study was conducted by interviewing the Director of Operations of Soegijapranata Social Foundation, Semarang Archidiose, Head of Al Rifdah Foundation of Semarang City, Representative of Badan Penyelenggara Jaminan Sosial (BPJS) of Semarang City Health, Head of the Double Disability Orphanage Management Bhakti Asih Kota Semarang, and the Chairman of the Double Disability Orphanage Management Al Rifdah Semarang City. The analysis used qualitative methodsThe results of the study indicate that there is no national regulation on health insurance rights for children with disability explicitly as mandated by the Constitution and Law Number 40 Year 2004 regarding National Social Security System. The obstacles that are experienced are in the case of regulations which regulating health insurance for children with disabilities are not harmonious and not clearly regulate about health insurance rights for children with disabilities. In addition, there are also obstacles in the form of administrative factors, the management of the Double Disability Children's Orphanage has difficulties in applying for children with disability who are cared or hospitalized just because there is no Identity Number and Family Card Number which is the main requirement to register the National Health Insurance program. Children with Disabilities in Al-Rifdah Dual Disability Orphanage have received the contribution of Health Insurance Semarang City, but this has not been obtained by Children with Disabilities in Double Disability Orphanage Management Bhakti Asih.